METHOD FOR KINETIC ARMOUR-PIERCING MUNITIONS EFFECTIVENESS ESTIMATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper presents a mathematical model and a computational module for armour-piercing munition (APM) effectiveness estimation. The topicality of this research arises from the necessity to automate the weaponeering process as part of Phase 3 of the Joint Targeting Cycle. The main objective of the study is to analyse the penetrator's structural material and munition's geometric characteristics impact over the depth of penetration into homogeneous steel armour plate Class I, in accordance with MIL-DTL-46100E/2008 standard.  Scientific methods analysis, math modelling, data collection, simulation and synthesis were used during the study. As a result, the following cconclusions were made: 1) the armour-piercing munitions’ effectiveness depends mainly on the ratio between penetrating rod’s density and the armour density, but not on the hardness of their penetrating elements; 2) the proposed model is an approximate empirical technique for armor-piercing munition effectiveness estimation; 3) iteratively finding solutions for different input variables makes it possible to determine the input conditions necessary to realize the desired damage effect on a target; 4) the computational module could be applied to the weaponeering process as part of the Joint Targeting Cycle.